Effects of high-intensity interval training on body composition, aerobic and anaerobic performance and plasma lipids in overweight/obese and normal-weight young men - Nejmeddine Ouerghi; Mohamed Kacem Ben Fradj; Ikram Bezrati; Marwa Khammassi; Moncef Feki; Naziha Kaabachi; Anissa Bouassida (Termedia Publishing House, 2017)
To examine the effects of short high-intensity interval training (HIIT) on body composition, physical performance and plasma lipids in overweight/obese compared to normal-weight young men. Nine overweight/ obese and nine normal-weight men (control group) aged 17 to 20 years underwent a HIIT programme three times per week for eight weeks. Body composition, indices of aerobic [maximal aerobic velocity (MAV) and maximal oxygen uptake (VO 2max )] and anaerobic [squat jump (SJ), counter-movement jump (CMJ), five-jump test (FJT), 10-m and 30-m sprint] performances, as well as fasting plasma lipids, were assessed in the two groups at PRE and POST HIIT. The HIIT programme resulted in significant reductions in body mass (-1.62%, P=0.016, ES=0.11) and fat mass (-1.59%, P=0.021, ES=0.23) in obese, but not in normal-weight subjects. MAV (+5.55%, P=0.005, ES=0.60 and +2.96%, P=0.009, ES=0.82), VO 2max (+5.27%, P=0.006, ES=0.63 and +2.88%, P=0.009, ES=0.41), FJT (+3.63%, P=0.005, ES=0.28 and +2.94%, P=0.009, ES=0.52), SJ (+4.92%, P=0.009, ES=0.25 and +6.94%, P=0.009, ES=0.70) and CMJ (+6.84%, P=0.014, ES=0.30 and +6.69%, P=0.002, ES=0.64) significantly increased in overweight/obese and normal-weight groups, respectively. 30-m sprint time significantly decreased in both groups (-1.77%, P=0.038, ES=0.12 and -0.72%, P=0.030, ES=0.16). Plasma total cholesterol (-11.8%, P=0.026, ES=0.96), LDL cholesterol (-11.9%, P=0.050, ES=0.77) and triglycerides (-21.3%, P=0.023, ES=1.08) significantly decreased in the obese group, but not in the normalweight group. The eight-week HIIT programme resulted in a slight improvement in physical fitness and a significant decrease in plasma lipids in the obese. Short duration HIIT may contribute to an improved cardiometabolic profile in the obese.